CovR and VicRK Regulate Cell Surface Biogenesis Genes Required for Biofilm Formation in Streptococcus mutans - Rafael Nóbrega Stipp; Heike Boisvert; Daniel J. Smıth; José Francisco Höfling; Margaret J. Duncan; Renata O. Mattos‐Graner (2013)
The two-component system VicRK and the orphan regulator CovR of Streptococcus mutans co-regulate a group of virulence genes associated with the synthesis of and interaction with extracellular polysaccharides of the biofilm matrix. Knockout mutants of vicK and covR display abnormal cell division and morphology phenotypes, although the gene function defects involved are as yet unknown. Using transcriptomic comparisons between parent strain UA159 with vicK (UAvic) or covR (UAcov) deletion mutants together with electrophoretic motility shift assays (EMSA), we identified genes directly regulated by both VicR and CovR with putative functions in cell wall/surface biogenesis, including gbpB, wapE, smaA, SMU.2146c, and lysM. Deletion mutants of genes regulated by VicR and CovR (wapE, lysM, smaA), or regulated only by VicR (SMU.2146c) or CovR (epsC) promoted significant alterations in biofilm initiation, including increased fragility, defects in microcolony formation, and atypical cell morphology and/or chaining. Significant reductions in mureinolytic activity and/or increases in DNA release during growth were observed in knockout mutants of smaA, wapE, lysM, SMU.2146c and epsC, implying roles in cell wall biogenesis. WapE and lysM mutations also affected cell hydrophobicity and sensitivity to osmotic or oxidative stress. Finally, vicR, covR and VicRK/CovR-targets (gbpB, wapE, smaA, SMU.2146c, lysM, epsC) are up-regulated in UA159 during biofilm initiation, in a sucrose-dependent manner. These data support a model in which VicRK and CovR coordinate cell division and surface biogenesis with the extracellular synthesis of polysaccharides, a process apparently required for formation of structurally stable biofilms in the presence of sucrose.